Progressive Multifocal Leukoencephalopathy with Negative JC Virus PCR following Treatment of Follicular Lymphoma: Implications for Biologics in the Era of Targeted Cancer Therapy - Kimberly A. Silverio; Shyam A. Patel (Case Reports in Oncological Medicine)
Anticancer therapy predisposes patients to infections by the immunosuppression that results from treatment. Although 85% of patients with progressive multifocal leukoencephalopathy (PML) have concurrent HIV/AIDS, PML can also develop in patients after they receive chemotherapy for cancer. The case herein describes a 69-year-old man with history of follicular lymphoma who presented with progressive dysarthria and right-sided paralysis. He received rituximab one year prior to presentation. PET scan suggested no recurrence of lymphoma. Cerebrospinal fluid (CSF) analysis was negative and showed fewer than 500 copies/mL of JC virus. However, brain biopsy showed chromatin margination and viropathic change within oligodendrocytes, confirming PML. He was started on mirtazapine and mefloquine with some clinical improvement. To our knowledge, this is the first case of rituximab-associated PML in a patient with negative JC virus PCR from the CSF. Recognition of PML in the differential of oncology patients with CNS symptoms is an important consideration as we enter the era of targeted therapy and personalized cancer medicine involving biologics. Furthermore, screening of patients for presence of subclinical JC viremia prior to the use of biologics may be an important component of assessing patient candidacy for these agents.